PEMBELAJARAN MENULIS LAPORAN DENGAN TEKNIK KOOPERATIF TERPADU MEMBACA DAN MENULIS SMPN 1 GEBANG - Atin, Sri (Universitas Wiralodra, 2021)
This research begins with the problem faced by the teacher, namely the lack of students' ability to understand the material. This study aims to improve the ability of grade IX students at SMPN 1 Gebang Cirebon Regency in understanding Indonesian subjects in the subject of